Treatment of symptomatic uterine fibroids with green tea extract: a pilot randomized controlled clinical study - Roshdy E; Rajaratnam V; Maitra S; Sabry M; Ait Allah AS; Al-Hendy A (Dove Medical Press, 2013)
Eman Roshdy,1,* Veera Rajaratnam,2,* Sarbani Maitra,2 Mohamed Sabry,3,4 Abdou S Ait Allah,3,4 Ayman Al-Hendy2 1Department of Public Health and Community Medicine, Sohag University, Sohag, Egypt; 2Department of Obstetrics and Gynecology, Meharry Medical College, Nashville, TN, USA; 3Department of Obstetrics and Gynecology, Sohag University, Sohag, Egypt; 4Ibn Sina IVF Center, Ibn Sina Hospital, Sohag, Egypt*These authors contributed equally to this workBackground: Uterine fibroids (UFs, also known as leiomyoma) affect 70% of reproductive-age women. Imposing a major burden on health-related quality-of-life (HRQL) of premenopausal women, UF is a public health concern. There are no effective medicinal treatment options currently available for women with symptomatic UF.Objectives: To evaluate the efficacy and safety of green tea extract (epigallocatechin gallate [EGCG]) on UF burden and quality of life in women with symptomatic UF, in a double-blinded, placebo-controlled randomized clinical trial.Methods: A total of 39 reproductive-age women (age 18–50 years, day 3 serum follicle-stimulating hormone < 10 mIU/mL) with symptomatic UF were recruited for this study. All subjects had at least one fibroid lesion 2 cm3 or larger, as confirmed by transvaginal ultrasonography. The subjects were randomized to oral daily treatment with either 800 mg of green tea extract (45% EGCG) or placebo (800 mg of brown rice) for 4 months, and UF volumes were measured at the end, also by transvaginal ultrasonography. The fibroid-specific symptom severity and HRQL of these UF patients were scored at each monthly visit, using the symptom severity and quality-of-life questionnaires. Student's t-test was used to evaluate statistical significance of treatment effect between the two groups.Results: Of the final 39 women recruited for the study, 33 were compliant and completed all five visits of the study. In the placebo group (n = 11), fibroid volume increased (24.3%) over the study period; however, patients randomized to green tea extract (n = 22, 800 mg/day) treatment showed significant reduction (32.6%, P = 0.0001) in total UF volume. In addition, EGCG treatment significantly reduced fibroid-specific symptom severity (32.4%, P = 0.0001) and induced significant improvement in HRQL (18.53%, P = 0.01) compared to the placebo group. Anemia also significantly improved by 0.7 g/dL (P = 0.02) in the EGCG treatment group, while average blood loss significantly decreased from 71 mL/month to 45 mL/month (P = 0.001). No adverse effects, endometrial hyperplasia, or other endometrial pathology were observed in either group.Conclusion: EGCG shows promise as a safe and effective therapeutic agent for women with symptomatic UFs. Such a simple, inexpensive, and orally administered therapy can improve women's health globally.Keywords: EGCG, leiomyoma, uterine fibroid, green tea, quality of life, pilot clinical study